2019
DOI: 10.1104/pp.18.01443
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Light Interacts with Time of Day and Leaf Development Stage to Reprogram Gene Expression

Abstract: Natural light environments are highly variable. Flexible adjustment between light energy utilization and photoprotection is therefore of vital importance for plant performance and fitness in the field. Short-term reactions to changing light intensity are triggered inside chloroplasts and leaves within seconds to minutes, whereas long-term adjustments proceed over hours and days, integrating multiple signals. While the mechanisms of long-term acclimation to light intensity have been studied by changing constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 182 publications
(224 reference statements)
17
69
0
Order By: Relevance
“…To validate the script and to provide interested users with a training dataset, we recorded an eleven-day fluctuating light experiment using mostly genotypes recently tested in a five day long Dynamic Environmental Photosynthetic Imaging run (Höhner et al, 2019) (Figure 6). In line with earlier studies, we found that all genotypes were affected by fluctuating light (Vialet-Chabrand et al, 2017;Schneider et al, 2019). Leaf surface area in WT plants decreased by more than half.…”
Section: Discussionsupporting
confidence: 92%
“…To validate the script and to provide interested users with a training dataset, we recorded an eleven-day fluctuating light experiment using mostly genotypes recently tested in a five day long Dynamic Environmental Photosynthetic Imaging run (Höhner et al, 2019) (Figure 6). In line with earlier studies, we found that all genotypes were affected by fluctuating light (Vialet-Chabrand et al, 2017;Schneider et al, 2019). Leaf surface area in WT plants decreased by more than half.…”
Section: Discussionsupporting
confidence: 92%
“…Nuclear gene expression reacts to irradiance in a highly dynamic way: hundreds of transcripts change within seconds-minutes after increases (Suzuki et al, 2015) and decreases (Crisp et al, 2017) in irradiance, suggesting that under a naturally fluctuating irradiance, gene expression will also be strongly affected. Indeed, a recent ground-breaking study (Schneider et al, 2019) has demonstrated the impact of fluctuating irradiance on gene expression in Arabidopsis. Short and strong light pulses, applied repeatedly for 3 d, caused a differential expression (DE) of ∼4000 genes, 75% of which were upregulated.…”
Section: Gene Expressionmentioning
confidence: 99%
“…The molecular response to fluctuating irradiance goes far beyond that of photooxidative stress: the data by Schneider et al (2019) suggested that processes regulating plant growth are affected on many levels, and that the expression of the respective genes is further under strong circadian and developmental control. However, altered gene expression does not necessarily equate altered protein abundance.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Correlation analysis revealed a greater reduction in Φ PSII under FL the further north on the globe the accession had originated from (Figure 8). This finding could potentially be explained by the following factors, considering that the main phase of vegetative growth of most Arabidopsis accessions is in early spring: (i) lower temperatures with increasing latitude, thus, accessions from further north may have optimized their photosynthesis to lower temperatures than those in our experiment (16 • C night, 21 • C day); (ii) differences in day length, because changes in gene expression that drive acclimation in response to FL have been shown to intercept with the circadian clock [3]; and/ or (iii) light intensity and availability.…”
Section: Can Evolutionary Adaptation Explain the Phenotype Of An Accementioning
confidence: 98%
“…However, plant responses strongly depend on the environment that plants have acclimated to, as they adjust their metabolism to cope most efficiently with the prevailing condition. Several recent studies focused on the model plant Arabidopsis thaliana (hereafter: Arabidopsis) under dynamic light [1][2][3], but these were restricted to few accessions only and thus did not assess the effects of genetic factors. The study of a larger set of genotypes is warranted, also because photosynthesis shows great intraspecific variation in Arabidopsis [4,5], and variation on the genetic level has been shown to translate more strongly into phenotypic variation under fluctuating light regimes (FL; [6]).…”
Section: Introductionmentioning
confidence: 99%